2024 transplant AI symposium: key AI models shaping the future of transplant care - Koivu, Annabel; Azarfar, Ghazal; Maleki, Saba; Sidhu, Aman; Bhat, Mamatha (Frontiers in Transplantation, 2026)
Experts in transplantation medicine and AI innovation came together to showcase advancements in AI applications with the potential to improve transplant outcomes. Ethical deployment, consolidation of multimodal data and supporting clinical decision making were among the themes addressed. Experts presented foundational models such as MedSAM for universal medical image segmentation, scPGT for single-cell genomics and Clinical Camel for clinical decision support, each demonstrating high capability and adaptability across transplant specialities. Experts highlighted future directions, considerations, and challenges for integrating these tools into clinical practice in an ethical and safe manner. We will summarize these themes as discussed at the Ajmera Transplant Centre's second annual Transplant AI Symposium.